Potensi rumput vetiver (Chrysopongon zizanoides L.) dan kangkung (Ipomoea aquatica Forsk.) sebagai agen fitoremediasi limbah industri kayu - Rahmawan, Ahmad Jamhari; Effendi, Hefni; Suprihatin, Suprihatin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Wood industry produces a large amount of waste water that contains various pollutants. These pollutants are mostly dangerous for the environment. This research work aims to analyze the ability of phytoremediation for reducing pollutants in wood industrial waste water. These experiments usee Chrysopongon zizanoides L. and Ipomoea aquatica Forsk as phytoremediation agents. The ability was evaluated from the improved quality of wood industrial wastewater and the growth rate of C. zizanioides (L.) and I. aquatica Forsk in wood industrial wastewater. Analysis was conducted by measuring the removal efficiency of pollutants in wood industrial wastewater, the correlation between the reduced pollutants concentrations in the waste water and plant growth rate. Furthermore, a mathematical model is developed to predict the potential of C. zizanioides (L.) and I. aquatica Forsk for wood industrial wastewater. The result showed that C.zizanioides L. and I aquatica Forsk were potential phytoremediation agent. The removal efficiency for C.zizanioides L. and I aquatica Forsk are respectively as follows: 66.19% and 41.18%, TSS 58.51% and 45.38%, COD 70.07% and 40.37%, Total Amonia Nitrogen (TAN) 63.70% and 66.96%, NH3 96.16% and 88.79%, and PO43- 53.90% and 38.38%. Relative Growth Rate (RGR) of C. zizanioides (0.011±0.002 g/day) is better than I. aquatica Forsk (0.007±0.001 g/day). Daily Growth Rate (DGR) of C. zizanioides (0.019±0.003 cm/day) is better than I. aquatica Forsk (0.012±0.006 cm/day). TSS, COD, NH3, NO3-, and phenol have a negative correlation to plant growth (based on wet weight and root length). The developed mathematical models can be used to predict the phytoremediation potential of C. zizanioides (L.) and I. aquatica Forsk in degrading COD, TSS, and phenols of wood industrial waste.